Cowpea (Vigna unguiculata L. Walp.) landraces in Mozambique and neighbouring Southern African countries harbour genetic loci with potential for climate adaptation - Mercy Wairimu Macharia; Leonardo Caproni; Marta Solemanegy; Robel Takele; Rogerio Marcos Chiulele; Paulino Munisse; Manuel Amane; Mario Enrico Pè; Roberto Buizza; Matteo Dell’Acqua (Communications Biology)
Abstract Large untapped potential for local climate adaptation is present in plant genetic resources maintained by smallholder farmers in Southern Africa. Cowpea (Vigna unguiculata L.Walp.), a staple crop for local farmers in the arid and semiarid regions of Southern Africa, is mostly unexplored by modern breeding approaches. In this paper, we assemble and characterize a collection of 389 cowpea accessions from Southern Africa, mainly landraces, including the entire ex-situ collection from the national Mozambique genebank. We use a genotyping-by-sequencing approach to describe the diversity in the collection and we concurrently characterize historical and projected climate at sampling points of landraces in search of genomic signatures of local adaptation. Our results show unique cowpea diversity in Mozambique, which can be partially put in relation with bioclimatic variation. The genotype-environment association approaches, Latent Factor Mixed Models (LFMM) and partial Redundancy Analysis (pRDA) allowed us to identify 36 genomic loci potentially involved in local climate adaptation. This included a region on chromosome 7 tagging four candidate genes linked to flowering and including a homolog of GIGANTEA, a gene regulating flowering time in response to day length and temperature in Arabidopsis. Finally, we estimated cowpea landraces adaptation to projected climate in the region, highlighting regions of maladaptation in southern Tanzania and Zimbabwe. Our results show that genetic resources maintained by farmers in Southern Africa bear traits for local climate adaptation and may contribute to enhancing the adaptability of cowpea to a shifting climate.